TEST OF RESISTANCE OF ALPUKAT (Persea americana mill) FRUIT EXTRACT ON THE GROWTH OF THE Streptococcus mutans - Putu Rusmiany; Ni Nyoman Nurdeviyanti; Ilma Yudistian; Agnesia Lorenza (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Streptococcus mutans is one of the normal flora living in the oral cavity, but in excessive amounts is the main causative agent of dental caries. The active compounds of alkaloids, saponins and quinones in avocado pulp extract is an antibacterial alternative that can inhibit the growth of Streptococcus mutans in the oral cavity. The aim of this research was to determine the inhibitory power that contain in avocado pulp against Streptococcus mutans . Materials and Methods: This study used 4 concentrations namely 25%, 50%, 75% and 100% with each repetition 4 times. Avocado pulp extraction was carried out by maceration method using 96% ethanol solvent. Inhibition zone testing was carried out using the Kirby baurer method. Results and Discussions: The zone of inhibition was determined using the Kruskal wallis test, which showed that there were significant differences in various concentrations against the growth of Streptococcus mutans bacteria. Avocado fruit pulp extract is able to inhibit the growth of Streptococcus mutans bacteria because avocado fruit pulp extract has active compounds that cause antibacterial activity. Active compounds of avocado fruit flesh that are efficacious as antibacterials are alkaloids, saponins and quinones. Conclusion: Avocado pulp extract has been proven to have an antibacterial effect against Streptococcus mutans with an effective concentration level of 100%. Increasing the concentration of avocado pulp extract was also shown to affect the diameter of Streptococcus mutans inhibition zone